Hourly modelling of Thermal Hydrogen electricity markets. Issue 3 (5th October 2020) - Moore, Jared; Meeks, Noah
Abstract: The hourly operation of Thermal Hydrogen electricity markets is modelled. The economic values for all applicable chemical commodities are quantified (syngas, ammonia, methanol and oxygen) and an hourly electricity model is constructed to mimic the dispatch of key technologies: bi-directional power plants, dual-fuel heating systems and plug-in fuel-cell hybrid electric vehicles. The operation of key technologies determines hourly electricity prices and an optimization model adjusts the capacity to minimize electricity prices yet allow all generators to recover costs. We examine 12 cost scenarios for renewables, nuclear and natural gas; the results demonstrate emissions-free, 'energy-only' electricity markets whose supply is largely dominated by renewables. The economic outcome is made possible in part by seizing the full supply-chain value from electrolysis (both hydrogen and oxygen), which allows an increased willingness to pay for (renewable) electricity. The wholesale electricity prices average $25–$45/MWh, or just slightly higher than the assumed levelized cost of renewable energy. This implies very competitive electricity prices, particularly given the lack of need for 'scarcity' pricing, capacity markets, dedicated electricity storage or underutilized electric transmission and distribution capacity. Graphical Abstract: Abstract : A Thermal Hydrogen economy could provide dispatchable energy supply and enable the electric grid to be largely powered by variable renewable energy without any dedicated grid-scale electricity storage. Model results show cost-competitiveness through a practical storage and distribution system via liquid hydrogen derivatives.